Angiotensin-converting enzyme inhibitory and antibacterial activities of low molecular weight peptides derived from spent brewer’s yeast - Hien, Pham Thi Thu; Hai Yen, Cao; Thi Hang Nga, Pham; Le Ha, Quan; Thi Thu, Dang (Vietnam Journal of Biotechnology, 2020)
According to the World Health Organization (WHO), hypertension is one of the most common chronic diseases. Cardiovascular disease causes 17.5 million deaths each year, in which hypertension is a direct cause to the death of up to 40%. This hypertension is caused by angiotensin-converting enzyme (ACE). ACE inhibitors consider as an effective therapy in  hypertension treatment.Many ACE inhibitors are synthesized by chemical pathways to control high blood pressure, however, these drugs often cause side effects. Therefore, in the last two decades, many authors have been interested in studying and producing a variety of ACE inhibitory peptides, which are naturally derived (plants, animals, and microorganisms) that help reduces blood pressure and less cause side effects. On the other hand, biologically active peptides that are resistant to pathogenic bacteria are also of special interest. In this study, we refer to the limited hydrolysis of spent brewer's yeast by proteases to collect peptides with a molecular size of ≤ 10, 5 and 3 kDa. Peptide fraction with molecular size  ≤ 10 kDa have ACE inhibitory activity. The results showed that smaller peptide fractions had higher ACE inhibitory activity. At concentration of 30 µg/mL, inhibitory activitiy of peptides with molecular sizes ≤ 10, 5, 3 kDa was 16.3, 27.7 and 32.7%, respectively, and the best IC50 was 48,85 µg/ml. The lowest peptide concentration for completely inhibition bacteria after 24 h of incubation was 30 mg/mL (V. cholerae), 35 mg/mL (E. coli) and 50 mg/mL (S. typhi).